Optimization Social Capital for Community Development in Peatland Use - Rositah, Erna; Bulkis, Sofyan (Journal of Food Security and Agriculture; Vol 1 No 2 (2017): Journal of Food Security and Agriculture, 2017)
The research objective is to formulate a model of community empowerment in the utilization of peat-based social capital. For this purpose, in the first year analyzing the socioeconomic and cultural conditions of society; patterns of use of peatlands and the community's social capital. Research using in-depth interviews, focus group discussions, observation and documentation. Data were analyzed descriptively qualitative. Socio-economic life of society Muara Siran and Kupang Baru very closely with fisheries and agriculture businesses. In accordance with the typology spans the majority of land in the form of peat swamp wetlands, fisheries sector is an important sector of society that is the source of livelihood. Agricultural land use is highly dependent on the changing seasons. Agriculture is growing paddy and upland farming. In the region of the village of Muara Siran there are three allocation function of the area, namely Zone Nature Reserve Sedulang Muara Kaman, Production Forest and Non Forest Cultivation Areas. While the village of Kupang Baru, only two, namely the Nature Reserve Sedulang Muara Kaman and Non Cultivation Region Forestry. Social capital of trust, cooperation and participation of the people tend to change and disorientation as greater authority in managing the Village Fund Allocation (ADD) by the Village Government. Social capital can be an important asset in the business community empowerment